Heterostructure‐Regulated Metal Silicates Composite Material for Enhancing the Lithium‐Ion Batteries Performance. Issue 6 (25th March 2022) - He, Lanqi; Wang, Qiushi; Feng, Jin; Xie, Zezhong; Zhou, Junyi; Fei, Fei
Abstract: Noticeable surface reaction in the energy storage mechanism has attracted tremendous research due to its relationship with electrochemical capacity and rate capability. In this work, in‐situ grown heterostructured metal silicates are prepared through a facile hydrothermal method. The composites are employed as anodes for supercapacitor and lithium‐ion batteries (LIBs). The ratio of cobalt and copper in the heterostructure has a significant effect on its properties, including porosity, electrical conductivity, and pseudo‐capacitance contribution during the energy storage process. The combination of metal silicates, heterostructure, and porous bio‐mass derived carbon into one system results in a unique electrode material with optimized reaction kinetics. The integration leads to a superior capacity and rate capability. Specifically, the cobalt silicate/copper silicate heterostructure composites present improved electrochemical performance as anode for LIBs and supercapacitor. For lithium‐ion storage, the B‐C@CoCuSi‐(3‐1) delivers a capacity of 574.5 mAh g −1 . When used as an anode material for supercapacitor, the B‐C@CoCuSi‐(1‐3) shows a capacitance of 80.4 F g −1 . Abstract : From bamboo to battery anode : In‐situ grown heterostructured metal silicates were prepared by a simple hydrothermal method on the surface of bamboo leave‐derived carbon. The synergetic effect between metal silicate and carbon material optimizes the reaction kinetics of the electrode material, which exhibits excellent performances in supercapacitor and lithium‐ion batteries.